ASSESSING THE FITNESS AND VALIDITY FOR DEPTH-DISTRIBUTION PATTERNS OF AVAILABLE MICRONUTRIENTS (Fe and Mn) OVER A TOPOSEQUENCE AT LAFIA NORTH-CENTRAL NIGERIA: APPLICATION OF EQUAL-AREA SPLINES (FUDMA JOURNAL OF SCIENCES, 2020)
The study focused on assessing the distribution of micronutrients (Fe, Mn) down the profile pits by using depth function of different level of soil depths (0-5, 5-15, 15-30, 30-60 and 60-90 cm) over a toposequence in faculty of agriculture Shabu-Lafia Campus. Three soil pits were sunk using Digital Elevation Model of the study area as guide for location of soil pits (upper, middle and lower slope). The results revealed that the cations (Fe and Mn) were low across the study area and in most cases Fe and Mn tend to decrease down the profile pits with few exceptions. The fitness of the models (R2 values)  ranged from 0.88-0.99 across the pits with the exception of Mn at profile three that the fitness of the model was not biased (R2 = 0.11). The spline functions were flexible and sensitive to changes (0-5 cm) of the micronutrients (Fe and Mn) movements down the profile pits therefore, they can be used in displaying the vertical variability of micronutrients within the soil of the study area.
Keywords: Micronutrients, Equal-area spline functions, Toposequence